Pendampingan Siswa Belajar Berbasis Belajar Kelompok untuk Meningkatkan Motivasi Belajar dan Prestasi Siswa - Anugraini, Asri Putri; Windriyani, Shinta Masitho; Pawitra, Paulus Rah Adi; Artanty, Ary (Pakis Journal Institute, 2025)
This community service activity aims to increase students' learning motivation and academic achievement through the implementation of group learning methods in the school environment. The group learning method is a collaborative approach that encourages students to discuss, share knowledge, and complete tasks together. The activity was carried out at State Elementary School 2 Watugede, Singosari district, with 30 student participants. The program implementation included training teachers on the effective application of the group learning method, assisting students during the group learning process, and evaluating the impact on students' motivation and learning outcomes. The results of the activity showed an increase in students' active participation in the learning process, improved learning motivation, as well as better academic results demonstrated by math exam scores. This activity proves that the group learning method can be a strategic alternative in efforts to improve the quality of learning.